2017
DOI: 10.7752/jpes.2017.s1014
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The purpose of this study, on the basis of the TAM, was to determine whether users would continue to use the sports-related mobile services by applying the measures of trust, usefulness, and attitude towards mobile sports content services. In order to find out the users' acceptance intention of mobile sports content, a survey aimed at 1,331 university students from 7 different districts of the nation was conducted. Statistical programs such as SPSS/pc Ver. 21.0, and AMOS 18.0 were used for data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Most studies had a higher proportion of females than males (n = 9), followed by studies that had parity in the sample (n = 5), four studies had a higher proportion of males while one study did not indicate the gender distribution of the sample [34]. Finally, all studies except Ha et al [42] and Yoo et al [53] reported some data on the age of the subjects. About half of the studies (n = 10) expressed age using a range, five studies showed age using mean (M = 24.58 years) and two studies did not specify the age [55,59].…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 95%
See 4 more Smart Citations
“…Most studies had a higher proportion of females than males (n = 9), followed by studies that had parity in the sample (n = 5), four studies had a higher proportion of males while one study did not indicate the gender distribution of the sample [34]. Finally, all studies except Ha et al [42] and Yoo et al [53] reported some data on the age of the subjects. About half of the studies (n = 10) expressed age using a range, five studies showed age using mean (M = 24.58 years) and two studies did not specify the age [55,59].…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 95%
“…The relationship between PU and ITU was evaluated in all of the studies analyzed finding different levels of relationship in the studies. Most studies (n = 9) found a moderate and significant influence between both variables with a range of Fisher's Z = 0.31-0.66 [1,[43][44][45]51,53,56,60,61]. Some studies found a significant high to very high ratio with a large influence of PU on ITU based on effect size values above 0.70 [52,59] and in two of the three models proposed by Kim et al [1].…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 95%
See 3 more Smart Citations